ANALISIS KELAYAKAN UNIT USAHA PENGELOLAAN SAMPAH PADA BADAN USAHA MILIK DESA “SIDO MAKMUR”, DESA GETASAN, KECAMATAN GETASAN, KABUPATENAN SEMARANG - Ambar Istiyani; Prasetyo Suryahadi Mahendra Lisaputra (Jurnal Riset Entrepreneurship, 2022)
This article aims to analyze the feasibility of “Sido Makmur” Village-Owned Enterprise (Badan Usaha Milik Desa/ BUMDesa), especially the Waste Management Business Unit. This unit has two stages of activities: Phase I is Waste Collection, and Phase II is Waste Segregation which includes converting the waste into goods with economic value. The Phase I program has been running since 2020 in one of the hamlets, and Phase II will soon be implemented. The feasibility analysis covers the aspects of Legal, Market and Marketing, Human Resource Management, Technical and Technology, Environments (Business, Economical, Socio-Cultural, Political, and Ecological), and Finance. Primary and secondary data in qualitative and quantitative data were analyzed using business feasibility analysis. More specifically, in Financial Aspect, the data were analyzed to determine the investment feasibility in terms of the Net Present Value, Internal Rate of Return, Average Rate of Return, Profitability Index, and Payback Period. The study results show that the Waste Management Business Unit in BUMDesa “Sido Makmur” is feasible. However, this business unit must maintain professionalism in providing its services to maintain customer loyalty. In addition, it is necessary to expand business units' operations, not only in one hamlet but also in other hamlets.